2013
DOI: 10.1111/jfs.12047
|View full text |Cite
|
Sign up to set email alerts
|

A Microbiological Comparison of Poultry Products Obtained from Farmers' Markets and Supermarkets in Pennsylvania

Abstract: The popularity of farmers' markets continues to rise in the U.S.A. Raw poultry products sold at farmers' markets are of particular concern due to the United States Department of Agriculture inspection exemption status afforded to many poultry vendors. Whole chicken from farmers' markets and supermarkets in Pennsylvania were evaluated for the prevalence of Campylobacter spp. and Salmonella spp. and demonstrated that 28% (28/100) and 90% (90/100) of chicken from farmers' markets, 20% (10/50) and 28% (14/50) of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 11 publications
6
41
1
Order By: Relevance
“…Similar practices have been observed in Italy and Spain (18). These findings are important considering recent data from the USA showing that poultry products purchased at farmers' markets had higher levels of bacteria such as Salmonella and Campylobacter when compared to those purchased from supermarkets (20). That study also found that organically produced poultry had higher levels of bacteria than did conventionally produced chickens, even when purchased from the supermarket.…”
Section: Discussion Purchase and Storage Behaviorsupporting
confidence: 69%
“…Similar practices have been observed in Italy and Spain (18). These findings are important considering recent data from the USA showing that poultry products purchased at farmers' markets had higher levels of bacteria such as Salmonella and Campylobacter when compared to those purchased from supermarkets (20). That study also found that organically produced poultry had higher levels of bacteria than did conventionally produced chickens, even when purchased from the supermarket.…”
Section: Discussion Purchase and Storage Behaviorsupporting
confidence: 69%
“…The results showed that lettuce obtained from the farmers' market had significantly higher (10 3 log CFU/g) E. coli concentrations compared to the lettuce obtained from the grocery stores (Sirsat and Neal, 2013). Similar conclusions were made by Scheinberg et al (2013) based on their investigation that demonstrated a higher incidence of Campylobacter spp. The hypothesis of this study was that farmers' market greens would have fewer bacteria because there is very little time between harvest and selling to the consumers.…”
Section: Farmers' Market Microbial Researchsupporting
confidence: 66%
“…Scheinberg et al . () also found that the prevalence of Salmonella were 28%, 20% and 8% in farmers' markets, organic, and conventional whole chickens respectively, in Pennsylvania region. Prevalence of Salmonella in our current study was similar to their finding.…”
Section: Discussionmentioning
confidence: 84%